PRODUCTION OF UNLEADED GASOLINE IN ASEAN COUNTRIES - A.S. Nasution; E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 2006)
Worldwide crude supply is experiencing a mod- est trend towards heavier and high sulfur content. The Middle East, being traditionally the world's ma- jor oil exporting region, will continue to be the princi- pal supplier of lower quality crude's in the future